Evaluation of desulfuring capacity of the Oryza sativa shell transformed as a activated porous material with potential use in the treatment of biogas. - José Luis Manrique Murillo (2020)
The Oryza sativahusk is usually discarded and incinerated without control, which is why in the present investigation it was given an alternative use by means of its transformation into different adsorbent materials coded as HRKOH, ACARROZ and ACFeO. (CAC for commercial activated carbon), the activation of the husk was carried out in a chemical way using Caustic Potassium at 40% this to lyse lignocellulosic structures; subsequently, a metal oxide was added chemically. The process was optimized through a multilevel factorial design, the maximum yield was recorded by the HRKOH material and was 94.45%, however, due to its low porosity and consequently low retention of pollutants, it was not considered a competent material., the field tests regarding the adsorption of hydrogen sulfide showed similar behaviors between ACarroz, ACFeO and CAC, so it was decided to contrast the material ACARROZ vs CAC by means of isotherms obtaining similar adjustments for both materials; the rice was better adjusted to the Langmuir isotherm showing an R2 of 0.9937 (R in Freundlich = 0.986), similar behavior showed the commercial coal to adjust with a coefficient of determination of 0.9965 for Langmuir and 0.957 for Freundlich.